The role of anthropogenic disturbance in the creation of a socio-ecological landscape - Fox, Helen Elizabeth (Rhodes University, Faculty of Science, Department of Environmental Science, 2005)
The aim of this thesis is to examine the role of anthropogenic disturbance in the creation of a socio-ecological landscape. Three key questions were answered: what impact has past anthropogenic disturbance had on present vegetative characteristics; what value did this disturbed landscape have to local people; how did the local peoples' worldviews and eco-cosmologies influence how they perceived, valued and managed their landscape? Research was based in a rural, predominantly amaXhosa village in the Kat River valley, Eastern Cape, South Africa. Four major landscape components characterised the environment, namely dense forests, former grazing lands, abandoned fields and old settlements. A combination of qualitative and quantitative methods were adopted, consisting of a vegetation and soil survey and social science methods including semistructured interviews, focus groups, transect walks and participant observation. The key finding was that anthropogenic disturbance is necessary to enhance the potential of the area to support human habitation. However, anthropogenic disturbance can have positive or negative effects for both local people and the environment. An intermediate level of disturbance is a key factor leading to a resilient socio-ecological system. Various anthropogenic disturbances have had significant affects on vegetation characteristics in terms of species richness, and a change in vegetation composition and species heights. Of the three anthropogenic landscapes examined, former grazing lands were the least intensively disturbed. They were also more species rich and structurally diverse than areas that were under agricultural production or used as a settlement. Dense forests, although the least desirable landscape to local people were, together with sacred pools, sources of ecosystem renewal and played a critical role during times of disturbance. Anthropogenic disturbance has added value to local people's livelihoods; this disturbance has resulted in a patchy landscape that supplies a wide variety of resources to local people. Local people are dependent on their environment for their basic needs; this has encouraged sustainable management practices. The local AmaXhosa still retain many elements of their traditional worldview, which has many characteristics of Animism. The environment is an integral component of their belief system and certain sites and species have significant cultural value and are protected.
Keywords: Human ecology -- South Africa -- Kat River Valley; Land use -- Environmental aspects-- -- South Africa -- Kat River Valley; Landscapes -- Social aspects -- South Africa -- Kat River Valley; Landscape ecology -- South Africa -- Kat River Valley; Vegetation and climate -- South Africa -- Kat River Valley; Xhosa (African people) -- Folklore; Kat River Valley (South Africa)